Behavioral readiness for circular economy in Albania: a consumer perspective - Dionizi, Brikene; Kalaj, Ermira H.; Avdullahi, Ajtene (Frontiers in Sustainability, 2025)
BackgroundThe transition to a circular economy is critical in achieving sustainable consumption, particularly in emerging economies such as Albania. While circular economy strategies have gained attention in policy and academic discourse, their success heavily depends on consumer engagement. Albania presents a unique context as a post-socialist, EU-inspiring country with evolving infrastructure and limited consumer exposure to circular economy practices.ObjectiveThis study investigates the readiness of Albanian consumers to engage with circular and sustainable practices, examining behavioral drivers, perceived barriers, and the influence of socio-demographic variables.MethodsA cross-sectional survey was conducted among respondents in North Albania, employing a structured questionnaire based on behavioral theories. Statistical analysis including regression models and structural equation modeling (SEM) is realized to assess relationships among latent variables.ResultsEmployment status, income and education significantly predicted circular economy knowledge and behavior. Key practices like sufficiency-driven consumption and donation of goods were associated with socio-economic variables, while motivational drivers such as environmental concern and practicality were more universally distributed. SEM results confirmed significant impacts of knowledge, behavior and practices on circular economy readiness, while preferences and influences had weaker predictive power. The findings inform context-specific policy and business interventions to support circular economy adoption in emerging economies.ConclusionBehavioral engagement in circular economy in Albania is shaped by both structural constraints and evolving socio-cultural values. Policy and business strategies must consider contextual realities and co-create circular solutions with customers to ensure adoption. The findings contribute to the behavioral understanding of circular economy readiness in emerging economies and provide a basis for targeted interventions in similar contexts.